Loss of MicroRNA‐489‐3p promotes osteosarcoma metastasis by activating PAX3‐MET pathway. Issue 4 (29th November 2016) - Liu, Qifei; Yang, Guochun; Qian, Yuying
Abstract : Osteosarcoma (OS) remains one deadly disease for many affected patients. MicroRNAs (miRNAs) are thought to have an important role in tumor metastasis by regulating diverse cellular pathways. Here, we describe the function and regulation network of miR‐489‐3p in osteosarcoma (OS) metastasis. MiR‐489‐3p expression was downregulated in OS cells especially in high metastatic potential cells and was also significantly decreased in metastatic lesions compared with their corresponding primary tumor samples. Both gain‐ and loss‐of‐function studies confirmed that miR‐489‐3p significantly suppressed OS cell invasion and metastasis both in vitro and in vivo. Mechanistically, paired box gene 3 (PAX3) was identified as a functional target of miR‐489‐3p in OS cells. MiR‐489‐3p inhibited OS metastasis by negatively regulating expression of PAX3. In addition, PAX3 expression was markedly higher in OS tissues than in adjacent non‐cancerous tissues. Transwell assays and in vivo metastasis assays demonstrated that overexpression of PAX3 significantly promoted the invasiveness and pulmonary metastasis of OS cells. On the other hand, downregulation of PAX3 markedly reduced cell metastatic potential. Mechanistic investigations indicated that prometastasis function of PAX3 was mediated by upregulating downstream target MET tyrosine kinase receptor. In conclusion, our results reveal that miR‐489‐3p‐PAX3‐MET signaling is critical to OS metastasis. Targeting the pathway described here may open new therapeutic prospects to restrict the metastatic potential of OS. © 2016 Wiley Periodicals, Inc.